The challenging approach towards a science - based standard for snowboard wrist guards - Senner, V.; Lehner, S.; Brügger, O. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
This study identified the wrist joint extension and the resulting bone stress for different age groups with and without the use of different type of wrist protection for backward falls. It provides the basis for design requirements and testing procedures of such devices thus making the formulation of ISO standards possible. The detailed description of this investigation is submitted for publication at the Journal of Sports Engineering and Technology --- The hosting University of Jyväskylä is planning to publish conference proceedings "Science and Nordic Skiing III". In case you are interested in this publication please contact the editors (Anni Hakkarainen anni.s.j.hakkarainen@jyu.fi) to become registered for the book.